A novel inhibitor of tumorspheres reveals the activation of the serine biosynthetic pathway upon mitochondrial inhibition. Issue 8 (23rd March 2019) - Subedi, Amit; Muroi, Makoto; Futamura, Yushi; Kawamura, Tatsuro; Aono, Harumi; Nishi, Mayuko; Ryo, Akihide; Watanabe, Nobumoto; Osada, Hiroyuki
Abstract : Differences in the metabolism of cancer cells or cancer stem cells (CSCs) as compared to normal cells have provided avenues to safely target cancers. To discover metabolic inhibitors of CSCs, we performed alkaline phosphatase‐ and tumoursphere‐based drug screening using induced cancer stem cell‐like cells. From the screening of a RIKEN NPDepo chemical library, we discovered NPD2381 as a novel and selective cancer‐stemness inhibitor that targets mitochondrial metabolism. Using our ChemProteoBase profiling, we found that NPD2381 increases the expression of enzymes within the serine biosynthesis pathway. We also found a role for serine in protecting cancer cells from mitochondrial inhibitors. Our results suggest the existence of a compensatory mechanism to increase the level of intracellular serine in response to mitochondrial inhibitors. Abstract :